Ex vivo confocal laser scanning microscopy: A diagnostic technique for easy real‐time evaluation of benign and malignant skin tumours. Issue 6 (24th March 2022) - Vladimirova, Gabriela; Ruini, Cristel; Kapp, Florian; Kendziora, Benjamin; Ergün, Ecem Z.; Bağcı, Işın S.; Krammer, Sebastian; Jastaneyah, Jawaher; Sattler, Elke C.; Flaig, Michael J.; French, Lars E.; Hartmann, Daniela
Abstract: Ex vivo confocal laser scanning microscopy (ex vivo CLSM) is a novel diagnostic tool for a quick bedside evaluation of freshly excised tissue, comparable to histology. We aimed to assess the sensitivity and specificity of ex vivo CLSM in detecting malignant features, to validate its reliability in identifying various skin tumours based on a combination of confocal features and to evaluate the digital staining mode (DS). One‐hundred twenty freshly excised skin samples from 91 patients were evaluated. Each lesion was screened for the presence of 23 predefined confocal criteria with ex vivo CLSM, followed by a histopathological examination. The diagnostic agreement between ex vivo CLSM and histology was 89.2%. The diagnostic accuracy of ex vivo CLSM in detecting malignancy reached a sensitivity of 98% and a specificity of 76%. Ex vivo CLSM enabled a rapid identification of the most common skin tumours, the tumour dignity and cytological features. The DS demonstrated a close resemblance to conventional histopathology. Abstract : The aim of this study was to prove the suitability of ex vivo confocal laser scanning microscopy for performing a fast and reliable microscopic examination of skin tumours in a real‐life setting. The results were verified by means of conventional histopathology. Furthermore, we examined the applicability of the newly added digital staining mode and could confirm its similarity to conventional histopathology.